Bio-inspired service management framework: green data-centres case study. (1st January 2013) - Carroll, Raymond; Balasubramaniam, Sasitharan; Suzuki, Junichi; Lee, Chonho; Donnelly, William; Botvich, Dmitri
The internet is evolving into a full-scale distributed service platform, offering a plethora of services from communications to business, entertainment, social connectivity and much more. The range of services and applications offered is diversifying, with new applications constantly emerging. For example, utility-based computing (e.g. HPC and cloud computing) which relies heavily on data-centre resources. These services will be more dynamic and sophisticated, providing a range of complex capabilities, which puts further burden on datacentres, in terms of supporting and managing these services. At the same time, society is becoming acutely aware of the significant energy burden the communications industry, and in particular data-centres, are becoming. With these trends in mind we propose a biologically inspired service framework that supports services which can autonomously carry out management functions. We then apply this framework to address the emerging problem of a sustainable future internet by autonomously migrating services to greener locations.